Increases in Reactive Oxygen Species Enhance Vascular Endothelial Cell Migration Through a Mechanism Dependent on the Transient Receptor Potential Melastatin 4 Ion Channel - Velasquez, L (Academic Press, 2015)
A hallmark of severe inflammation is reactive oxygen species (ROS) overproduction induced by increased inflammatory mediators secretion. During systemic inflammation, inflammation mediators circulating in the bloodstream interact with endothelial cells (ECs) raising intracellular oxidative stress at the endothelial monolayer. Oxidative stress mediates several pathological functions, including an exacerbated EC migration.Because cell migration critically depends on calcium channel-mediated Ca2+ influx, the molecular identification of the calcium channel involved in oxidative stress-modulated EC migration has been the subject of intense investigation.The transient receptor potential melastatin 4 (TRPM4) protein is a ROS-modulated non-selective cationic channel that performs several cell functions, including regulating intracellular Ca2+ overload and Ca2+ oscillation. This channel is expressed in multiple tissues, including ECs, and contributes to the migration of certain immune cells. However, whether the TRPM4 ion channel participates in oxidative stress-mediated EC migration is not known.Herein, we investigate whether oxidative stress initiates or enhances EC migration and study the role played by the ROS-modulated TRPM4 ion channel in oxidative stress-mediated EC migration.We demonstrate that oxidative stress enhances, but does not initiate, EC migration in a dose-dependent manner. Notably, we demonstrate that the TRPM4 ion channel is critical in promoting H2O2-enhanced EC migration.These results show that TRPM4 is a novel pharmacological target for the possible treatment of severe inflammation and other oxidative stress-mediated inflammatory diseases. © 2014 Elsevier Inc.